Constructivismo e intervención pedagógica: a propósito de quién construye - García Del Dujo, Ángel (Teoría de la Educación. Revista Interuniversitaria, 2009)
Among the multiple questions that arise from the practical application, both from the professional and research point of view, of the constructivist principles inspiring educational reform, there is one whose answer makes a difference in the orientation of both the theoretical analysis and practical functioning of the educational process. The question we are referring to is who is doing the constructing?. As opposed to the stances which would have the entire constructive activity fall on the internal control of the subject, the author defends the idea that there are different moments and spaces where constructive processes take place and there is always more than one constructor, which leads to the need for revising the concept of scaffolding.